A facile approach for the fabrication of nano-attapulgite/poly(vinyl pyrrolidone)/biopolymers core–sheath ultrafine fibrous mats for drug controlled release. Issue 55 (20th May 2016) - Zhu, Tonghe; Yu, Kui; Bhutto, M. Aqeel; Wang, Juan; Shen, Wei; Song, Wei; Zhou, Xiangxiang; EI-Hamshary, Hany; Al-Deyab, Salem S.; Mo, Xiumei
Abstract : Herein, we report a facile method for the fabrication of flurbiprofen axetil (FA)-loaded core–sheath composite ultrafine fibers for drug sustained release. Abstract : Herein, we report a facile method for the fabrication of flurbiprofen axetil (FA)-loaded core–sheath composite ultrafine fibers for drug sustained release. In our work, porous attapulgite nanorods (n-AT) were selected as carriers to load the model drug-flurbiprofen axetil (FA). The FA-loaded n-AT (FA@n-AT) with an optimized FA loading efficiency of 89.5% was initially dispersed in a poly(vinyl pyrrolidone) (PVP) solution as a core layer composite. Then, FA@n-AT/PVP was incorporated within biopolymer ultrafine fibers through coaxial electrospinning to form FA@n-AT/PVP/biopolymers core–sheath ultrafine fibers, which exhibited a uniform and smooth morphology. The loaded FA within the PVP/biopolymers coaxial ultrafine fibers showed a sustained release profile. Due to their significantly reduced burst-release profile, the developed FA@n-AT/PVP/biopolymers core–sheath ultrafine fibers are proposed to be a promising material in the field of pharmaceutical science.